2020
DOI: 10.1111/1365-2664.13596
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of semi‐natural habitats to biological control is dependent on sentinel prey type

Abstract: 1. It is widely recognized that landscape factors affect the biological control of weed seeds and insect pests in arable crops, but landscape effects have been found to be inconsistent between studies.2. Here, we compare six different types of sentinels (surrogate prey that was either live insects or seeds) to measure the effects of semi-natural habitats at field to landscape scales on levels of biological control in winter wheat in the UK. Sentinels were located in fields adjacent to three boundary types: gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 36 publications
(58 reference statements)
2
23
0
Order By: Relevance
“…Inconsistent effects of woody natural habitats on predation and parasitism have been reported previously (Karp et al, 2018). McHugh et al (2020) found that herbaceous habitat was positively associated with predation of aphids, while woody linear habitat was negatively associated with predation of aphids. There are also studies reporting positive associations between biocontrol rates and woody elements in the landscape (Bianchi et al, 2005;Bianchi, Goedhart and Baveco, 2008;Dainese et al, 2017;Dover, 2019).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Inconsistent effects of woody natural habitats on predation and parasitism have been reported previously (Karp et al, 2018). McHugh et al (2020) found that herbaceous habitat was positively associated with predation of aphids, while woody linear habitat was negatively associated with predation of aphids. There are also studies reporting positive associations between biocontrol rates and woody elements in the landscape (Bianchi et al, 2005;Bianchi, Goedhart and Baveco, 2008;Dainese et al, 2017;Dover, 2019).…”
Section: Discussionsupporting
confidence: 54%
“…However, to mimic natural conditions as much as possible I used one-day old eggs in my set-up, which emit stronger chemical cues than older eggs (Colazza et al, 2010). Fourth, identifying the natural enemies responsible for biocontrol is essential to make strong conclusions on biocontrol potential in any landscape, and to be able to target pest management at specific taxa (Zou et al, 2017;McHugh et al, 2020). However, direct observations to identify natural enemies responsible for predation or parasitism is laborious, time-consuming and difficult to conduct at six to eight sites at the same time (Zou et al, 2017).…”
Section: Arthropods and Biocontrol Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…In the next main stage of the process, the actual level of ecosystem service was measured. For pest control, this entailed developing and deploying a range of sentinel prey items designed to represent either invertebrate pests or weed seeds [41]. Studies were conducted in six economically important cropping systems: oilseed rape (two case studies), pumpkin (one case study), pear (one case study), olive (one case study), winter wheat (two case studies), and vine (one case study) that varied in farming intensity.…”
Section: Approach Based Upon Measurement Of Predation or Parasitismmentioning
confidence: 99%